Nutritional and toxicological studies of plant-based milk from kenaf (Hibiscus cannabinus L.) seeds - Zaini, Nur Syamimi (2022)
Kenaf (Hibiscus cannabinus L.) is an herbaceous fibre crop that belongs to the Malvaceae family with exceptional economic values. Kenaf seed has been reported to contain rich protein content, high unsaturated fatty acids, and plenty of beneficial bioactive compounds. This suggests that kenaf seeds may exert favourable health impacts such as antihypercholesterolemic and anti-oxidative effects on humans. Derived from the underexploited kenaf seeds, a novel nondairy beverage namely plant-based kenaf seed milk (KSM) can be produced. Being a novel food product, nutritional and safety evaluations of KSM are essential to ensure safe human consumption. Therefore, this study aimed: (i) to assess the nutritional and antinutritional composition of KSM (whole seed and dehulled seed varieties), (ii) to investigate the acute (14-day) oral toxicity effects of a single-dose KSM (whole seed variety) consumption at a dose of 9.2 ml/kg body weight, and (iii) to investigate the subacute (28-day) oral toxicity effects of daily KSM (whole seed variety) consumption at doses of 3.1, 6.1, and 9.2 ml/kg body weight. KSM (whole and dehulled seed varieties) was significantly higher in total carbohydrates and lower in crude protein than SM. KSM (whole seed variety) contained significantly lower crude fat content than SM, whereas crude fat in KSM (dehulled seed variety) was the highest. Glucose, fructose, and sucrose contents in KSM (whole seed variety) were significantly lower than in SM. KSM (dehulled seed variety) did not contain glucose but contained the highest fructose and sucrose. Potassium, phosphorus, and magnesium were the major minerals in KSM (whole and dehulled seed varieties), with phosphorus and magnesium present in significantly higher amounts than in SM. The total phenolic content and antioxidant activities of KSM (whole and dehulled seed varieties) were significantly higher than those of SM. KSM (whole and dehulled seed varieties) also presented lower lipid peroxidability than SM throughout the 3-day storage at chilled temperature. Qualitative analysis of chemical compounds by ultrahigh performance liquid chromatography-mass spectrometry revealed that KSM shared similarities in the presence of several chemical components with SM especially apigenin, citric acid, gluconic acid, palmitic acid, oleic acid, linoleic acid, and 13-Hydroxyoctadecadienoic acid. KSM (whole seed variety) was significantly lower in phytates, oxalates, and total saponins, and higher in total tannins than those of SM. Dehulling of kenaf seed significantly increased all antinutritional factors in KSM (dehulled seed variety). In the acute oral toxicity study, KSM (whole seed variety) was administered at a single high dose of 9.2 ml/kg body weight and animals were observed closely for 14 days. Next, in the subsequent subacute toxicity study, KSM (whole seed variety) was given at doses 3.1 ml/kg body weight (low), 6.1 ml/kg body weight (medium), and 9.2 ml/kg body weight (high) to different animal groups (n = 5) for consecutive 28 days. All treatments resulted in no toxicity signs in terms of growth, feed and water intakes, organ weights and histopathology, and mortality. Haematological parameters were unaffected by acute and subacute KSM consumption. Serum biochemical analysis revealed that subacute KSM consumption induced a significant favourable reduction in alanine aminotransferase level at the medium dose by 40%. Additionally, low-density lipoprotein cholesterol and total cholesterol increased significantly at the low dose (by approximately twice) and high dose (by 33.33%), respectively. Nonetheless, KSM was observed to have equivalent effects with SM in improving high-density lipoprotein cholesterol levels, at both low and medium doses. Hence, the oral lethal dose (LD50) and the no-observed-adverse-effectlevel (NOAEL) of KSM were greater than 9.2 ml/kg (or 1533 mg/kg) body weight. Further subchronic and chronic oral toxicity studies and human trials are recommended as there is the potential of developing KSM as a plant-based milk alternative.